Are there more tricks in the bag for treating thrombocytopenia? - Leavitt, Andrew D. (American Society for Clinical Investigation, 2010)
Thrombocytopenia, an abnormally low number of circulating platelets, results from inadequate platelet production, splenic platelet sequestration, or accelerated platelet clearance. Platelet transfusions are now the cornerstone for treating thrombocytopenia. With an ever-expanding demand for platelets, and with many patients having an inadequate response to platelet transfusions, new strategies are needed to treat thrombocytopenia. In this issue of the JCI, Fuentes et al. present provocative data regarding the use of direct megakaryocyte infusions as a novel approach to manage this vexing clinical problem.